Test Loop Termokopel Tipe K Dengan Kalibrator Jofra (JRFES (Jurnal Riset Fisika Edukasi dan Sains), 2019)
Thermocouple sensor loop test is performed to ensure the good condition of the sensor. For this reason, a thermocouple sensor loop test is performed using Jofra calibrator to avoid the sensor failing. Prepared Jofra temperature calibrator, set the temperature at Jofra according to the temperature range to be measured. At the voltage gauge (Fluke) set on the Der.C measure, the measuring probe is connected to the thermocouple in the position between the wires (+ and -) to measure the mV value or the temperature of Der.C. Then the sensor is inserted at the test point or location of the heater on the Jofra calibrator. 5 temperature inputs were carried out on the type K thermocouple loop test. The temperature of the K type thermocouple sensor can be used if the results of all the output temperatures on Jofra do not exceed the 5 ° C fair range, 4 temperature outputs are obtained where the sensitivity exceeds the 5 ° C reasonable limit, so the thermocouple sensor type K tested cannot be reused. Keywords:Sensor, Test Loop, Thermocouple  K,Temperature.